Mulher como sujeito da criminalidade: um estudo sobre a realidade de presidiárias do complexo Penal Dr. João Chaves Natal/ RN - Silva, Claudia Gabriele da (2009)
This work presents itself as a result of the research: Women as the subject of crime: a study on the complex reality of the criminal inmates Dr. John Keys - Natal / RN, done with women incarcerated in the Women's Pavilion Complex Criminal Dr. John Keys. Aimed to investigate the key determinants that lead women to enter the institution to be subject of crime. To better understand the object of our study, we start to understand and analyze the social reality, economic and cultural these women, as well as seizure of their family relationships and emotional, within a gender perspective and consider the analysis of major crimes committed and their determinations. In our study, it appears from successive approximations and procedures theoretical and methodological quality and quantity, we were privileged to documentary research, observation and semi-structured, beyond the theoretical foundation on the subject - that the question of increase in recent years, women in the criminal occurs as a result of socioeconomic reality experienced by those. At the same time, the study has also believe that poverty and crime are not phenomena of cause and effect, however, it is undeniable that the large number of prisoners (as) are poor and live situation of denial of rights. The main focus of the research points to the socio-emotional relationships, both marital and family as the main determinant for inclusion of women in crime, breaking with the myth that the woman is "fragile sex." And, more, points out that the woman in the process of emancipation and achievement of public spaces to commit a crime seek equal to the male. Moreover, the research also denounced in a prison system collapsed, and totally abandoned by the public. That denies all rights provided to prisoners (as), both inside and outside the "walls". It is a system that criminalizes and no one wants to fulfill its role, which is the functional rehabilitation and resocialization of (the) inmates (those). It is hoped that this work could contribute to the unveiling of the reality of women in the criminal - no pretension of exhausting it - and can also contribute to further studies on the subject